A functional Rev-erb alpha responsive element located in the human Rev-erb alpha promoter mediates a repressing activity. - Adelmant, G (1996)
Rev-erb alpha belongs to the nuclear receptor superfamily, which contains receptors for steroids, thyroid hormones, retinoic acid, and vitamin D, as well as "orphan" receptors. No ligand has been found for Rev-erb alpha to date, making it one of these orphan receptors. Similar to some other orphan receptors, Rev-erb alpha has been shown to bind DNA as a monomer on a specific sequence called a Rev-erb alpah responsive element (RevRE), but its transcriptional activity remains unclear. In this paper, we characterize a functional RevRE located in the human Rev-erb alpha promoter itself. We also present evidence that (i) Rev-erb alpha mediates transcriptional repression of its own promoter in vitro, (ii) this repressing effect strictly depends on the binding of Rev-erb alpha to its responsive element and is transferable to a heterologous promoter; and (iii) Rev-erb alpha binds to this responsive sequence as a homodimer.